2017
DOI: 10.18869/mjiri.31.2
|View full text |Cite
|
Sign up to set email alerts
|

Dual peer mentoring program: exploring the perceptions of mentors and mentees

Abstract: Background: Despite the advantages of dual peer mentoring, there are a few reports of implementing and evaluating such programs for medical students. This study aimed at exploring the perceptions of mentors and mentees about the dual peer mentoring program for the first year undergraduate medical students of Tehran University of Medical Sciences. Methods: This qualitative study was conducted at the end of the first year of implementing the mentoring program. All mentees and mentors were invited to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 21 publications
4
25
0
9
Order By: Relevance
“…Similarly, 7.7% of the mentees in the McLean [ 22 ] study reported the mentoring programme had helped them learn the “tricks of the trade”. Qualitative responses in the Abdolalizadeh et al [ 25 ] study also showed that the mentees perceived positive changes in their knowledge and attitude towards medical ethics and professionalism.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly, 7.7% of the mentees in the McLean [ 22 ] study reported the mentoring programme had helped them learn the “tricks of the trade”. Qualitative responses in the Abdolalizadeh et al [ 25 ] study also showed that the mentees perceived positive changes in their knowledge and attitude towards medical ethics and professionalism.…”
Section: Resultsmentioning
confidence: 95%
“…According to the Singh et al [ 23 ] paper, 24% of the medical students reported that the mentoring programme had helped them to settle in. The mentees in the Abdolalizadeh et al [ 25 ] study agreed that the psychosocial support provided by the mentors helped in the transition phase into medical school.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations